2018
DOI: 10.3390/antibiotics7010014
|View full text |Cite
|
Sign up to set email alerts
|

Fragment-Based Discovery of Inhibitors of the Bacterial DnaG-SSB Interaction

Abstract: In bacteria, the DnaG primase is responsible for synthesis of short RNA primers used to initiate chain extension by replicative DNA polymerase(s) during chromosomal replication. Among the proteins with which Escherichia coli DnaG interacts is the single-stranded DNA-binding protein, SSB. The C-terminal hexapeptide motif of SSB (DDDIPF; SSB-Ct) is highly conserved and is known to engage in essential interactions with many proteins in nucleic acid metabolism, including primase. Here, fragment-based screening by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 47 publications
0
25
0
Order By: Relevance
“…Chilingaryan et al have combined the saturation-transfer difference NMR (STD-NMR) and surface-plasmon resonance (SPR) to select small molecules that disrupt DnaG/SSB-Ct interaction. The molecules they found presented the simultaneous inhibition of other protein/SSB interactions due to the similar features of the SSB-Ct binding pocket in different proteins [ 69 ].…”
Section: Primase Interactions: An Opportunity To Disrupt Essentialmentioning
confidence: 99%
See 2 more Smart Citations
“…Chilingaryan et al have combined the saturation-transfer difference NMR (STD-NMR) and surface-plasmon resonance (SPR) to select small molecules that disrupt DnaG/SSB-Ct interaction. The molecules they found presented the simultaneous inhibition of other protein/SSB interactions due to the similar features of the SSB-Ct binding pocket in different proteins [ 69 ].…”
Section: Primase Interactions: An Opportunity To Disrupt Essentialmentioning
confidence: 99%
“…All three of these molecules were shown to bind to the active site of primase and are expected to interfere with the binding of substrate (ribonucleotides) or the DNA template [ 120 ]. Recently, Chilingaryan et al identified inhibitors of the primase/SSB-Ct interaction using fragment-based screening by a saturation-transfer difference nuclear magnetic resonance (STD-NMR) and surface plasmon resonance assays [ 69 ]. Compounds containing indole, 2-((1 H -indol-3-yl)thio)acetic acid and 1H-tetrazole scaffold especially para-fluorophenyl tetrazoles were identified as first-generation hits.…”
Section: Molecules That Were Found To Inhibit Dna Primasementioning
confidence: 99%
See 1 more Smart Citation
“…In the same year, Oakley et al implemented a fragment-based drug discovery (FBDD) approach in order to identify disruptors to the interaction of SSB with another of its partners, the DNA primase DnaG [ 81 ]. In this study, a SPR competition assay and a saturation-transfer difference NMR (STD-NMR) led to the identification of thirty fragments.…”
Section: Reviewmentioning
confidence: 99%
“…A method that combines NMR-fragment screening with an optimization using virtual screening (FBVS) was developed that selects inhibitors for DnaG-type DNA primase 20,21 . FBVS was found to be an effective method especially for challenging targets such as DNA primase 4,22 . This method yielded five small molecule inhibitors that target T7 DNA primase through a similar binding mechanism as shown by high field NMR 21 .…”
mentioning
confidence: 99%